The Interpretation of Euphemism in the Holy Quran - Al-Ahmad, Rahaf; Alharthi, Adel Awadh (International Journal of Language and Literary Studies, 2023)
The translation/interpretation of sacred texts is a thorny issue in translation studies as this type of translation involves dealing with words that represent real beliefs whose conveyance should be done accurately and adequately. The interpretation of the Holy Quran, which is the literal word of Allah, is no exception. This paper discusses the problematic issues and challenges in translating/interpreting sacred euphemistic expressions in the Holy Quran. It examines and analyzes these problems in terms of accuracy and quality. The data selected for this study comes from two different interpretations of two suras: Al-Nisa and Al-A'raf by Mustafa Khattab and Muhammad Mahmud Ghali. The taxonomy of translation techniques proposed by Vinay and Darbelnet (1995) is used as a theoretical framework in the current study. The study revealed that there were some interventional strategies used by the translators to transfer Quranic euphemistic expressions into English. These strategies include literal translation, modulation, equivalence, and adaptation. It is also found that literal translation was the most used technique, followed by modulation and equivalence. In some cases, literal translation of Euphemism in some Quranic verses didn't work because the intended meaning couldn't be achieved in the TL. The study contributes to our understanding of the problems posed by euphemistic expressions in religious texts and the possible strategies that can be adopted to solve these problems. Keywords: adequacy, euphemism, Holy Quran, translatability, Vinay and Darbelnet.